Optimal Choice of Transmission Parameters for LDPC-Coded CPM - Foruhandeh, Mahsa; Uysal, Murat; Altunbas, Ibrahim; Guven, Tuna; Gercek, Alper (MILCOM IEEE Military Communications Conference, 2014)
Continuous phase modulation (CPM) has attractive features such as spectral efficiency and constant envelope making it attractive for tactical waveforms. Serial concatenation of CPM with Low Density Parity Check Codes (LDPCs) provides a superior performance due to coding gains of this powerful code family. The choice of proper combination of LDPC and CPM is crucial to satisfy the targeted tactical waveform requirements of spectral efficiency, power efficiency and receiver complexity. In this paper, we address the problem of selecting the optimal transmission parameters in an LDPC-coded CPM system to satisfy a given spectral efficiency subject to a constraint on the demodulator complexity. Specifically, we consider modulation index, alphabet size, pulse shape duration, and code rate as transmission parameters. Utilizing a systematic search procedure, we identify the proper transmission parameters to achieve a targeted spectral efficiency and error rate. Finally, we present a Monte Carlo simulation study to demonstrate the performance of selected LDPC-CPM schemes with and without jamming.